1993
DOI: 10.1016/0014-5793(93)81776-v
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of tyrosine phosphorylated synthetic peptides by rat liver phosphotyrosine protein phosphatase isoenzymes

Abstract: Five phosphotyrosine-containing peptides have been synthesized by FMOC solid-phase peptide synthesis. These peptides correspond to the 4114 19 sequence of the Xenopus src oncogene, to the 1191 1220 sequence of the human EGF receptor precursor, to the 1146-1158 sequence of the human insulin receptor, to the 85(~865 sequence of the human/~-PDGF receptor, and to the 5-16 sequence of the erythrocyte human band 3. The peptides were used as substrates for activity assay of two isoforms (AcP1 and AcP2) of a low molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 26 publications
(22 reference statements)
3
48
0
3
Order By: Relevance
“…This enzyme actively dephosphorylates phosphotyrosine-containing proteins and peptides [24], and belongs to the non-receptor-like subfamily. The reaction mechanism involves the formation of a cysteinylphosphate intermediate and the enzyme has the signature [25] of members of the PTPase family in its active site.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme actively dephosphorylates phosphotyrosine-containing proteins and peptides [24], and belongs to the non-receptor-like subfamily. The reaction mechanism involves the formation of a cysteinylphosphate intermediate and the enzyme has the signature [25] of members of the PTPase family in its active site.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of B3P tyrosines prevents the binding of several glycolytic enzymes, causing high glycolytic rates in erytrocytes (Harrison et al 1991;Low et al 1987). Furthermore, Stefani et al (1993) demonstrated that the phosphotyrosine of a syntethic peptide corresponding to the sequence 5-16 of the B3P is much more efficiently hydrolyzed by the ACP 1 f isozyme than s isozyme. Therefore, as the ACP 1 f amount is strongly related to ACP 1 activity (Dissing and Svensmark 1990;Stefani et al 1993) and its activity is enhanced by ADA 1 *2 (Lucarini et al 1989), it is conceivable that this fact may result in a significantly dephosphorylation of tyrosine residue of B3P, slowing glycolytic rates in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These isozymes are expressed simultaneously in many tissues and they are characterized by different biological functions. ACP 1 f isozyme is the main responsible of the total ACP 1 activity (Dissing and Svensmark 1990;Fujimoto et al 1988;Stefani et al 1993). Since different effects on f and s isozymes activity result from modulation of ACP 1 enzymatic activity, C, CA and A phenotypes -characterized by lower concentrations of f isozymes -could be more susceptible to damage by oxidative events compared to the other phenotypes.…”
mentioning
confidence: 99%
“…It is likely, therefore, that they perform different physiological functions. Indeed, Stefani et al (1993) have shown that S and F isoforms have somewhat different interactions with the insulin receptor. This may explain the differences observed in our study between high and low S ACP1 genotypes.…”
Section: Discussionmentioning
confidence: 99%